2017
DOI: 10.1371/journal.pone.0182744
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-month contraceptive continuation among women initiating short- and long-acting reversible contraceptives in North Kivu, Democratic Republic of the Congo

Abstract: ContextDespite the inclusion of sexual and reproductive health (SRH) services in the minimum standards of health care in humanitarian settings, access to SRH services, and especially to contraception, is often compromised in war. Very little is known about continuation and switching of contraceptive methods in these settings. An evaluation of a contraceptive services program in North Kivu, Democratic Republic of the Congo (DRC) was conducted to measure 12-month contraceptive continuation by type of contracepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 27 publications
3
43
2
Order By: Relevance
“…All of these reasons explain why, in almost all studies, such as the Casey et al, study in the DRC (86.1% versus 78.0%) the rate of continuation of methods is higher in users of long-acting methods (implants and IUDs) than in users of short-acting methods (pills and injectables) [17]. In Senegal, in 2015, a study of 6927 women of childbearing age living in six urban sites showed that implants had the lowest 12-month discontinuation rate (6.3%), followed by intrauterine devices (IUDs) (18.4%).…”
Section: Effect Of Pp Interventions On Contraceptive Methods Discontimentioning
confidence: 99%
See 1 more Smart Citation
“…All of these reasons explain why, in almost all studies, such as the Casey et al, study in the DRC (86.1% versus 78.0%) the rate of continuation of methods is higher in users of long-acting methods (implants and IUDs) than in users of short-acting methods (pills and injectables) [17]. In Senegal, in 2015, a study of 6927 women of childbearing age living in six urban sites showed that implants had the lowest 12-month discontinuation rate (6.3%), followed by intrauterine devices (IUDs) (18.4%).…”
Section: Effect Of Pp Interventions On Contraceptive Methods Discontimentioning
confidence: 99%
“…There are also other factors which were reported by previous authors as in uencing contraceptive continuation. Among these factors we have the use of a short-acting method, the desire for pregnancy within two years [8], little or no sexual relations [9] and other socio-economic and demographic factors such as age, marital status, income, mass media-exposure, and partner involvement in decision making, and service quality [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, that could mean that 25 million of the 75 million unintended births are due to contraceptive discontinuation (2). Studies report discontinuation rates at 6-56% after just 12 months of contraceptive use (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Discontinuation, while still in need of pregnancy protection, increases with time beyond the most common measure of after 12 months of use (3,9,13).…”
mentioning
confidence: 99%
“…Discontinuation has been reported as significantly more common in sub-Saharan Africa as compared to other world regions (14). Often the most common reasons for discontinuation for those who wish to continue to prevent pregnancy is method related -such as health concerns or the experience of side effects (3,7,9,12,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation